Nuclear Security and HRD - Viet Nam’s Effort - Nu-Hoai-Vi Nguyen; Tan Huu Vuong (International Journal of Nuclear Security, 2016)
Viet Nam is expanding its nuclear energy program for the application in various areas including industries, agriculture, healthcare, education and research. Recognizing the importance of the nineteen issues laid out in the IAEA document “Milestones in Development of a National Infrastructure for Nuclear Power” [1], Vietnam is considering how to address these issues. This paper describes the establishment of nuclear security infrastructure in Viet Nam and how Viet Nam has addressed one of the nineteen issues, that is human resource development in nuclear energy in general and in nuclear security in particular.
Keywords: Nuclear security; human resouce development; nuclear security ỉnastructure